Pengaruh Media Animasi pada Model Pembelajaran Quantum Teaching terhadap Hasil Belajar Siswa Kelas X Mia 2 SMA Negeri 22 Makassar ( Studi pada Materi Pokok Ikatan Kimia ) - Mendila, Ayu Silviani; Ratnawaty, Ratnawaty; Ramdani, Ramdani (Jurusan Kimia FMIPA UNM, 2023)
This research is a quasi-experimental which aims to know the effect of using animation as the media in Quantum Teaching model to student’s learning achievement of Class X Mia 2 at SMA Negeri 22 Makassar. The research design used post-test, that is only control group design.The population of this research are students from Class X Mia 2 of SMA Negeri 22 Makassar which consists of four classes with 134 students. This research used cluster random sampling. The samples are from Class X Mia 2 which consists of 35 students classified as the experimental group and Class X Mia 1 which consists of 31 students classified as the control group. In experimental group, the students were taught by using animation as the media in Quantum Teaching,while control group were taught through Quantum Teaching without animation as the used media.This research used Quantum Teaching and animation media as the independent variables, while students’ learning achievement on main material of chemical bonds as the dependent variable. The data collection were obtained by giving post-test to measure students’ learning achievement on the main material of chemical bonds.The result of prerequisite test showed homogenous variants which were not distributed normally. Hypothesis were tested by Man Whitney test as explained: α = 0,05 were obtained from Zhitung= 3,76 > Ztabel = 1,65. To summarize from this research, there is an effect of using animation as the media in Quantum Teaching on students’ learning achievement of Class X Mia 2 at SMAN 22 Makassar (as applied in main material of chemical bonds).